indonesia - Saputra, Wisnu (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2023)
Consumption of foodstuffs such as meat, milk and other products of agrarian societies reduces consumption of fish. In 2019 Indonesia Indonesia was in 62nd position in terms of food security, even though fish itself has a long shelf-life and Indonesia itself has caught a lot of fish, this makes fishermen in Indonesia lose the market and it is even difficult to make a living, on the basis of this problem, the Aruna startup is here to make an application as a movement to overcome this problem, Aruna is a fisheries startup that helps fishermen to help fishermen compete globally. The theory applied in this research is the Diffusion of Innovation Theory. This research is a qualitative research and collects data through in-depth interviews, observations, and documentation. The results of this study are that the process of diffusion of innovations using the Aruna application in the Muara Angke coastal area has been going well with several obstacles experienced by fishermen. Keywords: Difusi Inovasi, Aruna, Nelayan, Teknologi.